Making a Victim of Yourself: Abortion, Performance and Liminal Theatrics - Henríquez Murgas, Tomás; Universidad de Chile, Santiago, Chile (Editorial Pontificia Universidad Javeriana, 2014)
Since 2012, the University Coordinator for Sexual Dissidence (CUDS) leads the campaign “Donate for an Illegal Abortion”, an artistic activism performance that tried to make visible the conflict related to abortion in Chile by means of several different disciplinary supports. They tried to position a debate by means of the collection of money on the streets for the performance of illegal abortions, video-clips, jingle songbooks, internet campaigns, training workshops for volunteers, among others. The divergences of the debate, however, tended to be neutralized by the conservative rhetoric of the vigilant consensus. In this way, the normality of the urban landscape is interrupted by performance acts that parody traditional schemes for the neoliberal rhetoric of consumption of solidarity. Also, this opens for us the possibility to relocate the intervention fields of the feminist dispute, widening its imaginaries and lusting bodies. Likewise, it is possible to redefine the traditional feminisms statutes, and reorder the regular landscape of the political economies of the image of pain and its visible bodies.